2001
DOI: 10.1080/00224540109600571
|View full text |Cite
|
Sign up to set email alerts
|

Gender Comparisons in the Private, Collective, and Allocentric Selves

Abstract: Researchers (e.g., M. B. Brewer & W. Gardner, 1996; H. C. Triandis, D. K. S. Chan, D. P. S. Bhawuk, S. Iwao, & J. P. B. Sinha, 1995) have suggested expansion of the standard model of individualism-collectivism to include people's close personal relationships in addition to their identification with in-groups. There has been considerable discussion of the hypothesis that women are more collective, interdependent, relational, and allocentric than men (e.g., S. E. Cross & L. Madson, 1997; Y. Kashima et al., 1995)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 34 publications
1
29
0
2
Order By: Relevance
“…This sense of self in relation differs from the collective self because it places primacy on interdependence between individuals rather than between an individual and a group (Madson & Trafimow, 2001). If an individual sees her own autonomy as restricted by social structures she may focus on interpersonal relationships as a means of and forum for personal achievement and advancement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This sense of self in relation differs from the collective self because it places primacy on interdependence between individuals rather than between an individual and a group (Madson & Trafimow, 2001). If an individual sees her own autonomy as restricted by social structures she may focus on interpersonal relationships as a means of and forum for personal achievement and advancement.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research indicates that while both men and women have interdependent aspects in their self-concept, men tend to be more group focused or collective and women appear more relational (Madson & Trafimow, 2001). Given this body of research, we predict that mothers will be more likely to emphasize social connectedness and interdependence than fathers.…”
Section: Values Of Individualism Vs Interdependencementioning
confidence: 97%
“…Previous empirical work supports the notion that men and women differ in the extent to which they see themselves and others as interdependent. For example, Madson and Trafimov (2001) found that women in the United States define themselves primarily by their relationships-as interdependent and connected to others (through both personal relationships and group identities)-whereas men define themselves primarily in terms of their uniqueness and independence from others.…”
Section: The Effects Of Intergroup Competition On Group Creativity: Smentioning
confidence: 99%
“…This task rests on the long sociological literature on the self and is based on the facts that each individual has numerous and multifarious selves and that these "self images" can be collected through self reporting (e.g., Madson & Trafimow, 2001). The TST requires participants to generate 20 self concepts that begin "I am .…”
Section: Studymentioning
confidence: 99%